2007
DOI: 10.1111/j.1365-2265.2007.02944.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes of endocrine function of adipose tissue in anorexia nervosa: comparison of circulating levels versus subcutaneous mRNA expression

Abstract: Local perturbations in resistin, adiponectin and interleukin-6 mRNA expression in subcutaneous adipose tissue are not reflected by its circulating levels. These changes could be involved in some local metabolic disturbances in subcutaneous adipose tissue of anorexia nervosa patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 33 publications
2
48
0
2
Order By: Relevance
“…Serum adiponectin has been found to be either increased Pannacciulli et al, 2003), normal (Iwahashi et al, 2003) or decreased (Tagami et al, 2004) in AN patients. Likewise, serum plasma resistin levels have been found to be either decreased (Dostalova et al, 2006) or normal (Dolezalova et al, 2007). These discrepancies suggest that some confounding factors, such as eating behaviors and/or physical activity level, could interfere with the results.…”
Section: Introductionmentioning
confidence: 87%
“…Serum adiponectin has been found to be either increased Pannacciulli et al, 2003), normal (Iwahashi et al, 2003) or decreased (Tagami et al, 2004) in AN patients. Likewise, serum plasma resistin levels have been found to be either decreased (Dostalova et al, 2006) or normal (Dolezalova et al, 2007). These discrepancies suggest that some confounding factors, such as eating behaviors and/or physical activity level, could interfere with the results.…”
Section: Introductionmentioning
confidence: 87%
“…by short-term caloric restriction or in the first weeks after a bariatric procedure (Mraz et al 2011, Trachta et al 2014. Moreover, subjects with severely depleted fat reserves as seen in mental anorexia also show increased production of proinflammatory adipokines (Dolezalova et al 2007). These data suggest that rapid or extreme changes in body fat content provoke immune response regardless of their direction.…”
Section: At As Immune Organmentioning
confidence: 97%
“…The cross-sectional design and other limitations of our study do not allow us to directly support this conclusion. Nevertheless, we have previously demonstrated that local changes in mRNA expression of some of the proinflammatory cytokines in subcutaneous adipose tissue of malnourished patients with anorexia nervosa share some similarities with changes in patients with obesity suggesting that local inflammatory response is present in adipose tissue of both cachectic and obese patients (21,22). Here, we showed that 2 weeks of VLCD did not significantly change serum MIC-1 levels in obese women with T2DM, but it significantly reduced serum MIC-1 in obese women without T2DM in spite of a similar reduction of body weight, serum cholesterol, serum triglycerides, and serum CRP during VLCD in both groups of patients.…”
Section: Discussionmentioning
confidence: 99%